Appraisal Burning Characteristic and Analysis Effect of Cavity in Scramjet Combustion Chamber - Le, Van-Minh; Dinh, Cong-Truong; Pham, Quoc-Khanh; Ta, Duc-Huy; Vo, Quang-Sang; Luu, Hong-Quan; Nguyen, The-Mich; Nguyen, Anh-Tuan (JST: Engineering And Technology For Sustainable Development, 2022)
The combustion chamber clearly plays an critical role in generating thrust force so the aircraft can move forward. A scramjet (supersonic combustion ramjet) is a variant of a ramjet airbreathing jet engine in which combustion takes place in supersonic airflow. Researchers are constantly working to improve the efficiency of ultrasonic combustion furnaces by various methods such as: optimize fuel injectors, optimize combustion chamber geometry design, create hole cavity. In this research, the characteristic of supersonic airflow were investigated, and a comparison between the standard chamber and advanced chamber was made to determine the effects of a circular hole (cavity) on pressure and velocity of the fuel mixture through the scramjet. Two dimensional Reynolds-Averaged Navier-Stokes governing(RANS) equations with k−ε turbulence model and finite rate/eddy dissipation chemistry model have been considered for modelling chemical reacting flows. From the comparison of numerical results, it is found that the development of recirculation regions and additional shock waves from the edge of cavity flame holder is increased and achieved stabilized combustion. From this research analysis, the performance of the scramjet engine with cavity is significantly improved as compared to the design without cavity.